Artes na educação infantil: um estudo das práticas pedagógicas do professor de escola pública - Carvalho, Maria Thereza Ferreira de (2010)
This work aim is to discuss the implications of teacher s formation in its practical classroom teaching considering the perspective of Critical Theory. Specifically this study identifies the elements of stimulation offered by the teacher choice associated with their formation. The research was focused on two public elementary schools, having the focus point as three teachers of those schools. It used the methodological principles of observation in the classroom as a procedure to identify and analyze the information collected. First of all, the study characterizes the aims of the teachers to attend the official requirements differing from classroom practice. Afterwards, compare the information collected evaluating the possible contributions in the process of learning and practicing arts. Based on the data analyzed it was found that the relation between the use of arts (visual, musical and body arts) and types of activities developed in classroom, identifies models and methods planned and the stimulation in its use in concrete learning situations. The alterations in educational politics face the work done in public infantile education. It leads to a reflection about the teacher formation and their needs to follow the official requirements that come from curricular changes made on this level of education. The adequacy of the teacher faces his or her conditions of working on many elements of difficulty, for example, their formation. The importance of art as an asset or in the contents of school curriculums it s confirmed by research and praised by the Brazilian legislative system through National Curriculum Parameters. Although, it s known that there is another possibility beyond what is proposed by laws meaning fruition of art as culture. For the enlightenment about the teachers practices, this work focus on the insertion of art and its necessary relation with other fields of study, starting with the perception of the own teachers about esthetical dimension. Putting it this way, the teachers formation and action their on the ambience and proposal of arts in classroom are discussed manly starting with the notion of experience, mass culture, pseudo formation theory and pseudo culture as concepts that reacts with the critical of Frankfurt theorists about late capitalism and its effects in education and the esthetic on contemporaneous society